2018
DOI: 10.1111/fwb.13237
|View full text |Cite
|
Sign up to set email alerts
|

Environmental heterogeneity and dispersal limitation explain different aspects of β‐diversity in Neotropical fish assemblages

Abstract: From a metacommunity perspective, patterns of β‐diversity emerge from the interplay between spatial and environmental processes. For obligate aquatic dispersers, river network constraints can be reflected in diversity patterns. Here, we aimed to determine the effects of environmental heterogeneity and spatial connectivity on β‐diversity components. We sampled fish assemblages in 21 sites across a longitudinal gradient. Beta‐diversity for taxonomic and functional composition among sites was decomposed into its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…This finding may occur because different sites are characterized by distinct environmental heterogeneity, so that assemblages with low trait diversity occurring at less heterogeneous sites are likely to be subsets of the high trait diversity assemblages that exist in highly heterogeneous sites (Rocha et al 2019). In line with our expectation and other trait‐based studies (Li et al 2019; Peláez and Pavanelli 2019), functional beta diversity (the overall and turnover components) was more strongly associated to local environmental variables. This indicates, as elaborated in the Habitat Templet Theory, that local environment conditions directly select species with specific trait combinations, but not species identity or lineages per se, to coexist within local assemblages (Southwood 1977).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding may occur because different sites are characterized by distinct environmental heterogeneity, so that assemblages with low trait diversity occurring at less heterogeneous sites are likely to be subsets of the high trait diversity assemblages that exist in highly heterogeneous sites (Rocha et al 2019). In line with our expectation and other trait‐based studies (Li et al 2019; Peláez and Pavanelli 2019), functional beta diversity (the overall and turnover components) was more strongly associated to local environmental variables. This indicates, as elaborated in the Habitat Templet Theory, that local environment conditions directly select species with specific trait combinations, but not species identity or lineages per se, to coexist within local assemblages (Southwood 1977).…”
Section: Discussionsupporting
confidence: 92%
“…As we expected, different dimensions of beta diversity showed various responses to the focal ecological factors, as also found in previous studies conducted in lentic (Heino and Tolonen 2017; Fu et al 2019) and lotic ecosystems (Li et al 2019; Peláez and Pavanelli 2019). Our results showed that both taxonomic and phylogenetic beta diversities were mainly contributed by turnover, and were more strongly affected by spatial factors (i.e., dispersal limitation).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The Amazon River Basin contains the highest fish species diversity of any region on earth (Reis et al, 2003). The biodiversity results from processes operating at multiple spatial and temporal scales (Peláez & Pavanelli, 2018). Heterogenous environments can contribute to maintain biodiversity (Peláez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%